Effect of initial water content and dry density on the self-healing of desiccation cracks in compacted hipparion red clay - Zhu, Yanbo; Zheng, Huitao; Lan, Hengxing; Liu, Yaowen; Li, Langping; Fu, Boyu; Du, Changcheng (Frontiers in Earth Science, 2022)
The self-healing of desiccation cracks in compacted clayey soils is important for mechanism revelation of cracking behavior in compacted soils. Although the crack self-healing behavior has been found, the influence of soil physical indices on it is still unclear, especially initial water content and dry density of specimen. This study aims to identify and evaluate the effect of initial water content and dry density on self-healing of desiccation cracks. Firstly, a series of desiccation tests were conducted on compacted Hipparion red clay specimens under different initial conditions. Secondly, the two-dimensional morphology of desiccation cracks and strain field changes on specimen surface were examined using the pore and crack analysis system and digital image correlation techniques. The result shows that the desiccation cracks on specimen surface exhibits self-healing behavior during drying. Based on the observed crack self-healing behavior, the desiccation cracking of compacted Hipparion red clay undergoes four stages including initiation, development, self-healing, and stabilization. During the self-healing stage, the critical water content for occurrence of crack self-healing and the crack self-healing amount referring to the crack ratio reduction from peak value to the stable value, are dry density dependent and water content dependent variables. In particular, the higher the initial water content and the lower the dry density of compacted specimen are, the larger the crack self-healing amount is. This crack self-healing difference in specimen with different initial conditions is caused by the vertical anisotropic shrinkage of substrate soil below non-propagating cracks due to its pore structure difference. This study provides a new perspective on the mechanism of desiccation crack in clayey soils affected by initial conditions.